(untitled) (University of Khartoum Engineering Journal, 2022)
Computer science and architecture is one of the fastest growing areas of knowledge and is beingintensely studied and researched. In the last few years, many new computer architectures were introduced by thecomputer industry. Also, many academic institutions and universities have developed their own architectures foreducational purposes and continued to advance their architectures through ongoing research and educationalprojects. This paper reports on the first Sudanese computer architecture that has been designed and implemented atthe University of Khartoum. This computer is a general purpose computer that executes one program at a timewithout pipelining. A reduced instruction set has been chosen such that the UofK computer would have the sameexecuting power as any other computer with a full instruction set. The instruction manipulations includearithmetic, logical, data transfer together with branching operations. The architecture provides for program inputfacilities, data input and output functions. The architecture behaviour was described using VHDL. The VHDLcode was then used to implement the design in a Field Programmable Gate Array to obtain a full functioningprototype. The computer has been successfully tested using sample programs. This implementation is consideredan important step towards building an educational computer architecture infrastructure for the University ofKhartoum and other Sudanese universities.